COMPARISON OF PARTICULATE MATTER (PM2.5) GROUND DATA AND SATELLITE DATA IN KANO STATE, NIGERIA - Idris, Maryam; Sani, Muawiya; Aliyu, Rakiya (FUDMA Journal of Sciences, 2025)
Air pollution, particularly fine particulate matter (PM₂.₅), poses significant environmental and health risks. This study compares satellite-derived PM₂.₅ data with ground-based measurements at different heights (2m, 5m, and 10m) to evaluate their accuracy and seasonal variations. Results indicate that during the dry season (Harmattan), PM₂.₅ concentrations reached 270 µg/m³, 117.11µg/m³ and 90µg/m³ highlighting increased pollution due to dust transport and atmospheric stability. In contrast, during the rainy season, PM₂.₅ levels dropped significantly to 6.59µg/m³, 12.5µg/m³, 14.2µg/m³ and 15.42µg/m³ demonstrating the effect of wet deposition. The study underscores the importance of integrating satellite and ground-based PM₂.₅ data for accurate air quality assessments and policy-making. It delves into the effects of particulate matter, sources of particulate matter on satellite data and elucidates meteorology and meteorological parameters used for describing and quantifying atmospheric conditions.
Keywords: Ground-based measurements; Harmattan (dry season); Meteorological parameters particulate matter; Satellite-derived data